STUDI KRITIS BAHAN AJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MATERI BERIBADAH QURBAN DI KELAS 5B SD ISLAM TECHNOPRENEUR AN NADWAH - Dudi Muharam; Siti Qomariyah; Andika Gumelar; Muhamad Naufal Firdaus; Sihabudin (STKIP Subang, 2026)
Qurban is a form of worship offered as a form of taqarrub to Allah, namely getting closer to Him and real evidence that Islam is a perfect religion and pays great attention to social relationships, such as qurban. This study aims to determine a critical study of Islamic Religious Education teaching materials on the qurban worship material for class 5B at SDI Technopreneur An Nadwah. This study uses a descriptive qualitative approach method. Data collection was obtained through observation, documentation and interviews. Data analysis techniques: data collection, reduction, display, conclusion and verification. Data validity test: Triangulation, dependability, confirmability and transferability. Research results: Overall, learning the qurban worship material for class 5B students at SD Islam Technopreneur An Nadwah shows suitability in integrating character values ​​such as sacrifice and social care, supported by interactive methods and standard learning resources that are aligned with the applicable PAI Curriculum. However, there are significant shortcomings in less specific learning objectives, minimal contextual material, cognitive-focused evaluation, and limited sources and methods due to limited facilities. Effective learning builds basic knowledge (conditions, pillars, wisdom) and basic character, but is less than optimal in internalizing spiritual-social values ​​due to the dominant theoretical approach and non-holistic evaluation. Qurban learning is expected to shape students with Islamic personalities (behaving according to Islam).